A room-temperature sodium metal anode enabled by a sodiophilic layer. (June 2018) - Tang, Shuai; Qiu, Zhi; Wang, Xue-Yin; Gu, Yu; Zhang, Xia-Guang; Wang, Wei-Wei; Yan, Jia-Wei; Zheng, Ming-Sen; Dong, Quan-Feng; Mao, Bing-Wei
Abstract: Sodium metal is a very promising anode for energy storage and conversion in the post lithium ion battery era because of its high capacity (1166 mA h g −1 ), earth-abundance and low cost. However, the sodium metal anode suffers from unstable plating and stripping cycling and thus low Coulombic efficiency. One of the important reasons for the situation is the high overpotential for sodium nucleation and thus non-uniform deposition and even dendrites growth. Herein we report a facile method by introducing a "sodiophilic" layer of Au-Na alloy onto the Cu substrate that acts as the current collector to significantly reduce the nucleation overpotential. Thus, the sodium metal can be plated on and stripped from the modified current collector with good reversibility. The average Coulombic efficiency maintains 99.8% at the current of 2.0 mA cm −2 for 300 cycles. As a proof of concept, an anode-free full cell consisting of Cu@Au and presodiated FeS2 was assembled. Our work demonstrates the great importance of sodiophilic modification of substrate to the deposition process for sodium metal battery. Graphical abstract: fx1 Highlights: A sodiophilic Au layer having large binding energy with Na is introduced on the surface of Cu substrate. Au layer converts to a sodiophilic Au-Na layer due to alloying reaction with Na. Na can be plated on and stripped from the Cu@Au-Na substrate with a very high coulombic efficiency.